PREVALENCE OF MUSCULOSKELETAL DISORDER AND ITS DETERMINANT FACTORS AMONG DENTISTS: PREVALENSI MUSCULOSKELETAL DISORDER DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PADA DOKTER GIGI - Rachmawati, Yuanita Lely; Palupi, Dyah Nawang (TALENTA, 2018)
Musculoskeletal pain has been found to be a health problem for dental practitioners. If the disorders ignored, cumulative damage may result in lowered productivity and even early retirement, injury or disability. Reported prevalence musculoskeletal disorders (MSD) to the dental practitioners in Indonesia were not yet known for certain. The aims of this study were to determine the prevalence of MSD among dental practitioners in Malang, Indonesia and to identify the factors that affect the occurrence of MSD. The study design was a cross-sectional analysis. The participants were 95 general dentists in Malang-Indonesia who asked self-administrated filled out the questionnaire. The questionnaire contained inquiry about: age, gender, body mass index, the time-lapse as a dentist, working hours, number of patients, working with an assistant, exercises on the sidelines of working time, sports activity, working position and asking whether they were suffering from musculoskeletal disorders in the last 12 months. The data analyzed by descriptive and logistic regression. The results showed 58.9% dentists complaint musculoskeletal pain in the last 12 months. The common complaints felt by the participants were back pain 34.6%, shoulder 18,9% and neck 16.9%. The determinants factors statistically significant correlations on MSD were working hours per week, working position, and exercises on sidelines working time.